FOOD SOUVENIRS FROM BALI – WHAT MATTERS FOR TOURISTS FROM JAKARTA? - Diena Mutiara Lemy; Debbie Darmawan; Julio Putra Tjokromulia (Journal of Business on Hospitality and Tourism, 2019)
Bali is one of the popular destinations in Indonesia. It is not only popular for the international tourists, but also for domestic tourist. One large segment of Bali domestic tourist is from Jakarta. This segment like to buy food souvenir from Bali, even though the food do not presenting Balinese local food. The purpose of this research is to determine the degree of influence from brand image, brand awareness and dimension of food souvenirs from Bali towards buying decisions of Tourist from Jakarta when they are in Bali. Usually, product with good brand image and good brand awareness could attract people to buy the products.This research uses descriptive quantitative approach, where the data is collected through questionnaire and observations. To analyze the data, multiple linear regression analysis using SPSS program was applied. The result will determine if the brand awareness and brand image of food souvenirs really influence buying decision of tourist from Jakarta or not. The benefit of this research is expected that it will be a beneficial insight for the tourism industry in Bali in making a strategy for increasing tourist expenditure, from the food souvenirs sector.